A framework for uncertainty quantification of mixed lubrication of conformal contacts in multilevel systems. (February 2023) - Zhu, Jiaxing; Li, Huacong; Wei, Shijie; Song, Shanshan
Highlights: A framework for uncertainty investigation in gear pump-journal bearings system is presented. A deterministic model to solve system level lubrication problem based on multidisciplinary theory is established. An efficient surrogate model based Monte Carlo simulation of uncertainty analysis examines the variation of model outputs. Most important uncertain parameters on different system working conditions are determined. Introduced methodologies can be used for many other complex(multi-level) mechanical systems. Abstract: A typical complex mechanical system usually should be treated as a multilevel system consists of several subsystems with hierarchical relationship. In response to the situation that conformal contact analysis for complex mechanical system is rarely considered as a system-level problem, this paper presents an efficient framework for uncertainty quantification of conformal contacts in complex system. The framework integrates tribological estimators, system-level simulation strategy and data-driven approach, which also involves the modeling of numerical computational models, the combination of numerical model with commercial software and the investigation of uncertainties in system. Moreover, it facilitates the embedding of surrogate model in the problem solving process to reduce the computational burden. The proposed framework is then applied to the uncertain quantification for an aero engine pump-journal bearing system with conformal contact. Results show the framework makes uncertainty quantification feasible for constrained computational budgets of numerical evaluation of complex mechanical systems with conformal contacts.